Circulação de herpesvírus na comunidade indígena Haliti-Paresí - Rossi, Elaine Menezes (2022)
Introduction - Infections caused by human herpesvirus are considered the most frequent sexually transmitted infection in the world, with a wide spectrum of clinical involvement, acute and reactive infections, high transmissibility and even orofacial and anogenital lesions caused by human Alphaherpesvirus 1 (HSV) and 2 (HSV-2), respectively. In the case of indigenous populations, herpetic infections further aggravate the health situation of this population, given that they have some of the worst social indicators in the country, in addition to inequity in access to health services and increased vulnerabilities. Objective - Thus, we sought to investigate the seroprevalence of HSV-1 and HSV-2 infection in Haliti-Paresí indigenous people in Mato Grosso, Brazil. Methods - Its development was based on cross-sectional research. Data collection was carried out in 2015, in nine villages of the Haliti-Paresí ethnic group, located in the municipality of Campo Novo do Parecis, Mato Grosso. Questionnaires were applied to collect sociodemographic data, with subsequent collection of peripheral blood for the constitution of the Biobank. The variables investigated were reactivation by herpes type 1 and herpes type 2 and sociodemographic variables: sex, age group, schooling, family income, number of residents in the household, carrying out activities outside the village, number of sexual partners, condom use and manifestations. clinical symptoms in the last thirty days, such as: fever, headache, myalgia, dizziness, low back pain, diarrhea, nausea, oral and/or genital lesions and abdominal pain. Bivariate analysis, Likelihood Ratio Test and Fisher's Exact Test were used, with significant Chisquare at 5%. Sample analysis was performed in May 2020, at the Viral Immunology laboratory of Instituto Oswaldo Cruz, using an enzyme-linked immunosorbent assay (ELISA) to determine Immunoglobulin G (IgG) in herpes types 1 and 2. Results - 100 indigenous people participated in the study, with a prevalence of females (60%), adults aged between 18 and 59 years (61%), low schooling (67%) and monthly income of 1 to 2 minimum wages (83%). Most respondents claimed not to carry out activities outside the village (79%), reported having only one sexual partner (73%) and did not have the habit of using condoms during sexual intercourse (70%). Among the interviewees, 97% were seropositive for herpes type 1 and 24% for type 2. In the analysis of clinical aspects, there was a statistically significant association between self-reported autogenital lesion and clinical manifestations fever (p<0.01), myalgia (p=0.01), oral lesion (p=0.01) and reactivation by herpes type 1 and type 2 (p=0.039). Conclusion - In view of this, the high seroprevalence of herpesvirus in this ethnic group, associated with several symptoms, indicates the urgency of actions aimed at preventing and controlling the spread of human herpesviruses, taking into account socio-cultural aspects of this population.